2020
DOI: 10.3389/fnut.2020.580551
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Risk to Food Safety

Abstract: The COVID-19 pandemic has brought about a consideration of our understanding of transmission of the causal agent, SARS-CoV-2 to humans and its potential effect on food safety and food security. The main routes of transmission are reported to be person-to-person, by respiratory droplets and to a lesser degree, by fomites. Concerns have been raised on the possibility of transmission via food and food packaging and whether the virus poses a risk to food safety. The current contribution provides an exposé of updat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 53 publications
1
51
0
2
Order By: Relevance
“…Beyond contamination of common surfaces such as packaging materials and counters, SARS-CoV-2 has been recovered at refrigeration (4 °C) and freezing temperatures (0 °C and −80 °C) on some meats and food contact surfaces. These results may be limited in their translation to real world situations as virus recovery was measured with methods less specific than plaque assays (TCID 50 ), methods that do not assess for infectious virus (nucleic acid amplification tests), or methods using conditions that are not common to real-world environments (incubation in viral recovery media at constant temperature and humidity) [ 8 , 9 ], the results of which can be misinterpreted. Several press reports regarding the detection of the virus on imported salmon, shrimp, chicken, and ice cream have suggested that food can become contaminated at unknown points along the food supply chain ( accessed on 17 March 2021; accessed on 17 March 2021) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond contamination of common surfaces such as packaging materials and counters, SARS-CoV-2 has been recovered at refrigeration (4 °C) and freezing temperatures (0 °C and −80 °C) on some meats and food contact surfaces. These results may be limited in their translation to real world situations as virus recovery was measured with methods less specific than plaque assays (TCID 50 ), methods that do not assess for infectious virus (nucleic acid amplification tests), or methods using conditions that are not common to real-world environments (incubation in viral recovery media at constant temperature and humidity) [ 8 , 9 ], the results of which can be misinterpreted. Several press reports regarding the detection of the virus on imported salmon, shrimp, chicken, and ice cream have suggested that food can become contaminated at unknown points along the food supply chain ( accessed on 17 March 2021; accessed on 17 March 2021) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Viral transmission may be affected by various environmental factors, including temperature, humidity, and route of transmission ( Chin et al, 2020 ; Ratnesar-Shumate et al, 2020 ; Ren et al, 2020 ). Additionally, with the current industry standards for food manufacturing ( Anelich, 2020 ), the risk of food contamination through exposure to contaminated products and contamination of the production line is likely low and thus, public health threat due to the consumption of contaminated food is likely limited. However, given that commercially produced beverages are often produced on a large-scale and exported to other countries, the finding of this study demonstrating that SARS-CoV-2 is stable in optimal conditions for more than 2 months indicates that a sufficient amount of infectious virus may potentially lead to virus transmission, and this points to possible exposure through the handling of contaminated food and beverages.…”
Section: Discussionmentioning
confidence: 99%
“…75 , 76 The average risk of contamination with food or food packaging is evaluated to be lower. 77
Figure 12.2 Main steps of sous vide cooking to lower viral contamination risks for food products.
…”
Section: Food Packaging Applications and Sars-cov-2mentioning
confidence: 99%
“…The particle size of SARS-CoV-2 ranges from 50 to 200 nm. 77 Ignatov has reported the exact size as 120 nm. 80 The use of nanomaterials based on antiviral activity provided inactivation of some viruses in chicken embryo models and shrimp samples.…”
Section: Limitation Of Sars-cov-2 Spreadmentioning
confidence: 99%